Essential Factors Determining the Quality of Population Life - Lialikova, Valentina Ivanovna; Kalinina, Jelena Nikolajevna; Žičkienė, Skaidrė (Socialiniai tyrimai, 2018)
The purpose of the article is to generalize methods used in the world practice for assessing the quality of life, to identify the main factors of differentiation of the quality of life in the regions of the Republic of Belarus. The object of research – the quality of life. Methods of research: analysis, systematization and synthesis of scientific literature, methods of multivariate statistical analysis.The priority of social policy in developed countries is to employ the economic and social potential of population so that population can achieve life satisfaction. The question is how to assess the quality of life and life satisfaction. Common economic indicators, such as GDP, inflation and budget deficit, the trade balance are far from reflecting the true state of the economy, as the real state of the economy can be reflected using the indicators of people’s well-being.Annual global studies are conducted to monitor welfare and quality of life in countries around the world. Different methods are used to measure the quality of life, and they provide an opportunity to explore objective and subjective factors, their impact on the level and quality of life, compare the situation in different countries of the world, identify problems and trends.The urgency of improving the quality of life of the population in Belarus is confirmed by the National Strategy for Sustainable Social and Economic Development of the Republic of Belarus for the period until 2020. The main provisions in this program are: 1) raising the level of the nation’s well-being, overcoming poverty, changing consumption patterns; 2) priority development of health, education, science, culture – the most important spheres of the spiritual life of society, factors of long-term productivity growth, creative activity, and the evolution of the national economy; 3) improving the demographic situation, promoting sustainable development of settlements. In the framework of this program, the priority tasks include, first of all, raising real money incomes and reducing the number of poor people, creating conditions and providing citizens with equal opportunities for material and social well-being, raising the education level index, creating an effective health system and strengthening its capacity.In assessing the quality of life an important task is to form a system of initial indicators. One of the most complete and up-to-date is the system “Basic indicators of the quality of life in the market economy”, developed at the Center for Economic Conjuncture and Forecasting under the Ministry of Economy of the Russian Federation in 1992. This system of indicators was developed by the Ministry of Economy of the Russian Federation and the Goskomstat of Russia, coordinated with the interested ministries and departments, regional administrations and put into operation in 1993. The proposed set of indicators consists of five blocks, which include such indicators:Quality of the population. The coefficients of natural and migratory growth (per 1,000 population), the infant mortality rate (per 1,000 births), the expected average life expectancy, the coefficient of demographic burden, the number of marriages and divorces (per 1,000 population), the proportion of employees with higher education in organizations (% ).Living standards of the population. The average monthly wage (in thousands of Belarusian rubles), the provision of housing (square meters per capita), the provision of cars (per 1,000 people), the gross regional product, retail turnover, the volume of paid services per capita (in thousands of Belarusian rubles).The quality of the social sphere (social security). The level of registered unemployment (%), the availability of doctors and nurses (per 10,000 population), the number of victims during industrial accidents (per 10,000 workers), the number of crimes (per 10,000 people).Quality of the ecological niche (environment). Emissions of pollutants discharged from stationary sources (tons per square meter of area), emissions of water pollution – the share of polluted water in the total volume of waste water discharged into surface water bodies (decubic meters per 1square kilometers of area).5. The cultural state of society. The number of visits to theaters, museums.A comparative analysis of the quality of life in the regions of the Republic of Belarus for 2011–2015 was conducted using a system of indicators that reflects the quality of life in the studied regions. Based on the methods of multivariate statistical analysis, ratings of the regions were constructed and a breakdown into groups was carried out according to the homogeneous value of the integrated indicator of the regions.The analysis revealed the necessary actions that must be taken to improve the quality of life in the Republic of Belarus: increased incomes, solution of demographic and employment issues, growth of retail turnover, better opportunities for higher education and subsequent employment, improvements in nation’s health and medical care system.This scientific article is funded by the Research Council of Lithuania according to the project “Social Innovations in the Context of Regional Development: Socioeconomic Development and Improvement of Life Quality in the Low Urbanized Areas of Countryside” (2017–2018), registration No. TAP LB-17-012.
Keywords: quality of life; quality of life indicators; measurement of quality of life